A method of constructing a front interface to reduce rocking chair zinc ion negative electrode side reactions and improve efficiency

CN116864640BActive Publication Date: 2026-10-27HUAZHONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310830026.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2026-10-27
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

迄今为止,还没有摇椅式锌负极材料的前沿界面抑制副反应的相关报道

Benefits of technology

[0022]1、本发明构建的前沿界面修饰的摇椅式锌负极具有摇椅式锌负极本征的优势,不会破坏材料本身原有的特性,通过适当的前沿界面修饰处理处理之后,仍然能保持原材料的原有的结构,且保证了摇椅式锌负极不会产生枝晶的本征优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116864640B_ABST
    Figure CN116864640B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of aqueous zinc ion battery, and discloses a method for constructing front interface to reduce rocking chair type zinc ion negative electrode side reaction and improve efficiency. The rocking chair type aqueous zinc ion battery negative electrode composite material constructed based on the method is obtained by loading and / or modifying interface material components on the rocking chair type zinc ion battery negative electrode active material. The interface material components are electrochemically inert and can remain stable in the aqueous electrolyte, and do not provide capacity. The present application improves the composition and structure of the rocking chair type zinc ion battery negative electrode active material, uses the material stable in the aqueous zinc ion battery as the front interface of the rocking chair type negative electrode of the aqueous zinc ion battery, blocks the direct contact of the rocking chair type negative electrode with the electrolyte, thereby inhibiting the side reaction and enhancing the efficiency and cycle stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aqueous zinc-ion battery technology. More specifically, it relates to a method for constructing a leading-edge interface to reduce rocking-chair zinc-ion anode side reactions and improve efficiency. The resulting rocking-chair aqueous zinc-ion battery anode composite material is obtained by constructing a leading-edge interface, thereby reducing rocking-chair zinc-ion anode side reactions and improving efficiency. Background Technology

[0002] Aqueous zinc-ion batteries (ZIBs) have attracted much attention due to their inherent safety characteristics, cost-effectiveness, pollution-free operation, moderate energy density, and simple manufacturing process. In particular, research on electrode materials for aqueous ZIBs has become increasingly in-depth in recent years. To date, Zn-based… 2+ For electroplating / stripping of aqueous zinc-ion batteries, zinc metal (Zn foil, Zn powder, etc.) is commonly used as the anode material due to its low potential (-0.76V vs. SHE), high conductivity (resistivity 5.91μΩ·cm), high theoretical capacity (820mAh g⁻¹), and high stability in water. However, zinc metal anodes still face the following bottlenecks in practical applications: i) Uneven plating / stripping behavior leads to zinc dendrite growth, which may puncture the separator and cause internal short circuits; ii) Corrosion reactions occur on the zinc surface, accelerating Zn consumption, resulting in decreased battery performance and low coulombic efficiency; iii) Hydrogen evolution side reactions not only lead to low electroplating / stripping efficiency but also disrupt the local electrolyte pH, forming insoluble byproducts, resulting in poor reversibility and short lifespan of the zinc metal anode. Therefore, for aqueous zinc-ion batteries, the conventional zinc metal anode suffers from dendrite growth, corrosion, and passivation problems during cycling, affecting the practical application of aqueous zinc-ion batteries.

[0003] Looking back at the development of lithium-ion batteries, the use of intercalated graphite materials instead of lithium metal as the anode cleverly solved the problem caused by lithium dendrites, achieving a safer "rocking chair" commercial lithium-ion battery. Drawing on successful and feasible experiences, manufacturing zinc-free "rocking chair" ZIBs may break through the bottleneck of zinc metal anodes. The key is to develop suitable anode materials, such as Zn... 2+ Insertion / extraction provides reversible sites. Therefore, exploring modification strategies for rocking chair zinc anodes to obtain ZIBs with high stability and long service life is a research hotspot.

[0004] Existing technologies have developed various rocking-chair zinc anode materials, such as titanium-based, copper-based, bismuth-based, molybdenum-based, tungsten-based, and vanadium-based materials. However, these traditional rocking-chair materials react directly with the solvent in the electrolyte (i.e., water), leading to material instability. As the material continuously contacts the solvent during charging and discharging, side reactions occur repeatedly during zinc storage, further resulting in low efficiency and poor cycle stability of the rocking-chair anode. In other words, traditional rocking-chair anode materials are prone to side reactions and structural instability under traditional low-discharge conditions (the voltage at which anode materials typically operate is often below 1V), leading to capacity decay. This phenomenon is particularly prominent in aqueous zinc-ion batteries (ZIBs), significantly impacting their lifespan. This is because aqueous ZIBs use water as a solvent, which reacts with these rocking-chair zinc anode materials (while other batteries using organic solvents, such as lithium-ion batteries, do not have this problem). Therefore, there is a need to develop advanced rocking chair zinc anode materials with advantages such as high capacity, high initial coulombic efficiency, stable host structure and long life.

[0005] On the other hand, interface engineering is an effective strategy for regulating zinc ion intercalation behavior, which can effectively mitigate side reactions at the rocking-chair zinc anode interface. It can reduce direct contact between the anode and water molecules in the electrolyte, suppress side reactions on the anode surface, and improve cycle performance. To date, there are no reports on cutting-edge interface-based suppression of side reactions in rocking-chair zinc anode materials. Summary of the Invention

[0006] To address the aforementioned deficiencies or improvement needs of existing technologies, the present invention aims to provide a method for constructing a leading-edge interface to reduce side reactions and improve efficiency in rocking-chair zinc-ion batteries. This method involves improving the composition and structure of the active material of the rocking-chair zinc-ion battery anode, loading and / or modifying interface material components on the active material, and using a material stable in aqueous zinc-ion batteries as the leading-edge interface of the rocking-chair anode. This prevents direct contact between the rocking-chair anode and the electrolyte, thereby suppressing side reactions and enhancing the material's efficiency and cycle stability. The present invention further improves the intrinsic stability of the material by directly constructing a leading-edge interface at the interface of the rocking-chair anode material in aqueous zinc-ion batteries.

[0007] To achieve the above objectives, according to one aspect of the present invention, a rocking chair-type aqueous zinc-ion battery negative electrode composite material is provided, characterized in that the composite material is obtained by loading and / or modifying the interface material composition on the rocking chair-type zinc-ion battery negative electrode active material; wherein,

[0008] The interface material is electrochemically inert and stable in the aqueous electrolyte, and does not provide capacity.

[0009] As a further preferred embodiment of the present invention, the interface material is selected from at least one of activated carbon, TiO2, ZnS, ZnSe, Bi2O3, TiF4, Zn3(PO4)2, and ZnB4O7.

[0010] As a further preferred embodiment of the present invention, the rocking chair-type zinc-ion battery negative electrode active material is at least one of the following: titanium-based rocking chair-type zinc-ion battery negative electrode active material, copper-based rocking chair-type zinc-ion battery negative electrode active material, bismuth-based rocking chair-type zinc-ion battery negative electrode active material, molybdenum-based rocking chair-type zinc-ion battery negative electrode active material, tungsten-based rocking chair-type zinc-ion battery negative electrode active material, and vanadium-based rocking chair-type zinc-ion battery negative electrode active material.

[0011] As a further preferred embodiment of the present invention, the rocking chair-type aqueous zinc-ion battery negative electrode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery negative electrode active material using a vacuum sintering method; the sintering temperature used in the vacuum sintering method is preferably 500℃~900℃.

[0012] As a further preferred embodiment of the present invention, the rocking chair-type aqueous zinc-ion battery negative electrode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery negative electrode active material by plasma treatment; preferably, the plasma treatment uses a power of 100W to 300W and a treatment time of 10min to 120min.

[0013] As a further preferred embodiment of the present invention, the rocking chair-type aqueous zinc-ion battery negative electrode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery negative electrode active material using a high-energy ball milling method; preferably, the high-energy ball milling method uses a rotation speed of 500 r / min to 1500 r / min and a processing time of 2 h to 100 h.

[0014] As a further preferred embodiment of the present invention, the rocking chair-type aqueous zinc-ion battery negative electrode composite material is obtained by first coating the rocking chair-type zinc-ion battery negative electrode active material on one side of the current collector, and then coating the interface material component on the same side of the current collector to cover the rocking chair-type zinc-ion battery negative electrode active material.

[0015] As a further preferred embodiment of the present invention, the rocking chair-type aqueous zinc-ion battery negative electrode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery negative electrode active material under inert atmosphere by using a tube furnace calcination method; the sintering temperature used in the tube furnace calcination method is preferably 500℃~900℃; the inert atmosphere is preferably argon.

[0016] As a further preferred embodiment of the present invention, the discharge capacity of the rocking chair-type aqueous zinc-ion battery negative electrode composite material is 200–280 mAh g. -1 The initial coulomb efficiency is 60-90%, and it can achieve a coulomb efficiency of 0.5A g. -1 It has a capacity retention of 62-90% after 1000 cycles.

[0017] According to another aspect of the present invention, the present invention provides the application of the above-mentioned rocking chair-type aqueous zinc-ion battery negative electrode composite material as a rocking chair-type aqueous zinc-ion battery negative electrode.

[0018] Compared with existing technologies, the technical solutions conceived in this invention modify traditional rocking chair-type zinc-ion battery anode active materials into novel surface-interface modified rocking chair-type aqueous zinc-ion battery anode composite materials through processes such as vacuum sintering, plasma methods, direct coating, and high-energy ball milling. A leading interface is constructed at the surface of the anode active material. Unlike traditional rocking chair-type materials, which react directly with the solvent in the electrolyte, leading to material instability and continuous side reactions during charging and discharging, resulting in low efficiency and poor cycle stability of the rocking chair-type anode, the composite material obtained in this invention constructs a leading interface at the surface (i.e., a rocking chair-type zinc-ion battery anode material modified with a leading interface). The materials used in this leading interface are interfacial materials that are electrochemically inert and stable, without providing capacity. Consequently, the resulting rocking chair-type aqueous zinc-ion battery anode composite material exhibits high efficiency and stable cycle performance in the electrolyte. This invention, through surface treatment and the physical barrier and chemical bonding effects of the surface, greatly improves the intrinsic properties of the active material. The modified rocking chair zinc anode can maintain electrochemical stability in zinc-ion battery anodes, improve the storage efficiency of electrode materials, and enhance the cycle stability of materials.

[0019] This invention provides a rapid, efficient, and directionally controlled method for constructing the leading edge interface of a rocking chair zinc-ion battery anode material, a method known in existing technologies. Anode materials for rocking chair batteries are often powdered active materials. This invention, in particular, utilizes room temperature or high temperature methods (such as vacuum sintering, plasma methods, direct coating, and high-energy ball milling) to efficiently control the leading edge interface of the rocking chair zinc anode, enabling the construction of a composite material for rocking chair aqueous zinc-ion batteries, which is highly convenient for practical applications. Taking plasma methods, direct coating methods, and high-energy ball milling as examples, they can be synthesized at room temperature, greatly reducing equipment costs. Furthermore, these methods are simple to operate, have short production cycles, low preparation costs, and meet the requirements for industrial production.

[0020] Based on the rocking chair-type aqueous zinc-ion battery anode composite material obtained by this invention, the rocking chair-type zinc anode front interface is modified by controlling the composition of the interface material. After interface modification, the rocking chair-type material will not react directly with the solvent in the electrolyte, which can improve the structural stability of the material. During subsequent charge and discharge processes, the material does not come into direct contact with the solvent, which can avoid side reactions during zinc storage, further resulting in high efficiency and good cycle stability of the rocking chair-type anode. The rocking chair-type material front interface after advanced interface modification obtained by this invention has the essential characteristics of a rocking chair-type zinc anode, enabling it to suppress side reactions and improve cycle stability when used as a zinc-ion battery anode. By introducing a stable front interface that does not react with the electrolyte at the electrode material interface, the modified rocking chair-type zinc anode composite structure can stabilize the structure of the rocking chair-type zinc anode during cycling.

[0021] Specifically, compared with the prior art, the present invention can achieve the following beneficial effects:

[0022] 1. The rocking-chair zinc anode with front-edge interface modification constructed in this invention has the inherent advantages of rocking-chair zinc anodes. It does not damage the original properties of the material itself. After appropriate front-edge interface modification treatment, it can still maintain the original structure of the raw material and ensure that the rocking-chair zinc anode will not generate dendrites.

[0023] 2. The rocking chair-type material prepared by this invention, after interface modification, will not react directly with the solvent in the electrolyte. This leads to improved material structural stability. During subsequent charge and discharge processes, the material does not come into direct contact with the solvent, thus avoiding side reactions during zinc storage. This further results in high efficiency and good cycle stability of the rocking chair-type negative electrode.

[0024] 3. This invention uses an inert and stable (i.e., does not react with water) and non-reactive (i.e. does not provide capacity) interface material in an aqueous electrolyte. Through interface engineering, the interface structure and composition are controlled by adjusting the modification of the leading interface, thereby achieving interface coupling, regulating the interface ion transport process, stabilizing the structure, and greatly reducing side reactions.

[0025] 4. This invention is applicable to various rocking chair zinc anode materials known in the prior art, such as titanium-based materials, copper-based materials, bismuth-based materials, molybdenum-based materials, tungsten-based materials, and vanadium-based materials. The interface material composition can be flexibly combined with any known rocking chair zinc-ion battery anode active material according to actual needs. All of these combinations can reduce side reactions and improve efficiency in rocking chair zinc-ion batteries because these interface material components can all exert electrochemical inertness and maintain a stable mechanism of action.

[0026] 5. The method involved in this invention has high versatility, strong adaptability, good compatibility, and generates high economic value and benefits. The method is simple to operate, has a short cycle time, and low cost, reducing the economic cost pressure caused by material degradation, meeting the requirements of industrial production, and promoting the industrialization and application of zinc-ion battery electrodes. In particular, this invention can employ room temperature treatment methods such as plasma methods, direct coating methods, and high-energy ball milling methods, which are more convenient, have lower energy consumption, and lower costs compared to existing high-temperature synthesis processes.

[0027] Traditional rocking-chair zinc anode materials react directly with the solvent in the electrolyte (i.e., water), leading to material instability. As the material continuously contacts the solvent during charge and discharge, side reactions occur repeatedly during zinc storage, further resulting in low efficiency and poor cycle stability of the rocking-chair anode. To date, there are no reports on advanced interfacial suppression of side reactions in rocking-chair zinc anode materials. This invention, based on traditional rocking-chair zinc anode materials, obtains an advanced rocking-chair zinc anode material with advantages such as high capacity, high initial coulombic efficiency, stable host structure, and long lifetime by loading and modifying the interfacial material composition (which can be achieved through various means).

[0028] In summary, this invention efficiently achieves interface modification and structural engineering of advanced rocking chair zinc anode materials. Based on a material surface interface modification strategy, it regulates the interface structure engineering of the rocking chair zinc anode, thereby improving the cycle stability of the rocking chair zinc anode through interface modification. This invention can reduce side reactions and improve efficiency in rocking chair zinc-ion batteries. Based on this invention, it is possible to modify low-quality aqueous rocking chair zinc anodes in aqueous zinc-ion batteries, significantly improving the capacity, rate performance, and cycle performance of zinc-ion batteries. Attached Figure Description

[0029] Figure 1 The image is a scanning electron microscope image of the rocking chair-shaped negative electrode front interface material provided in Embodiment 1 of the present invention.

[0030] Figure 2 This is a scanning electron microscope image of the frontal interface material of the negative electrode without the construction of a rocking chair-shaped negative electrode provided in Comparative Example 1 of the present invention.

[0031] Figure 3 Transmission electron microscope (TEM) image of the rocking chair-shaped negative electrode front interface material provided in Embodiment 1 of the present invention.

[0032] Figure 4 This is a transmission electron microscope (TEM) image of the frontal interface material of the negative electrode without the construction of a rocking chair-shaped negative electrode provided in Comparative Example 1 of the present invention.

[0033] Figure 5The X-ray diffraction results of the rocking chair-shaped negative electrode front interface material provided in Embodiment 1 of the present invention and the comparison of the results with the standard peaks of TiO2 and TiSe2.

[0034] Figure 6 The X-ray diffraction results of the present invention without the construction of the rocking chair-shaped negative electrode front interface material are shown in Comparative Example 1 of the present invention, and the results are compared with the TiSe2 standard peak.

[0035] Figure 7 The electrochemical efficiency of the rocking chair-shaped negative electrode front interface material provided in Embodiment 1 of the present invention.

[0036] Figure 8 The electrochemical efficiency of the present invention without constructing a rocking chair-shaped negative electrode front interface material is provided in Comparative Example 1 of the present invention.

[0037] Figure 9 Cyclic voltammetry curves for constructing a rocking chair-shaped negative electrode front interface material provided in Embodiment 1 of the present invention.

[0038] Figure 10 The cyclic voltammetry curves provided in Comparative Example 1 of the present invention do not show the construction of a rocking chair-shaped negative electrode leading-edge interface material.

[0039] Figure 11 The charge-discharge curves for constructing the rocking chair-shaped negative electrode front interface material provided in Embodiment 1 of the present invention are shown.

[0040] Figure 12 The charge-discharge curves provided in Comparative Example 1 of the present invention do not show the construction of a rocking chair-shaped negative electrode leading-edge interface material.

[0041] Figure 13 The AC impedance diagram for constructing the rocking chair-shaped negative electrode front interface material provided in Embodiment 1 of the present invention.

[0042] Figure 14 The AC impedance diagram provided in Comparative Example 1 of the present invention does not show the construction of a rocking chair-shaped negative electrode leading-edge interface material. Detailed Implementation

[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0044] Example 1

[0045] Preparation of titanium-based (TiSe2 / TiO2) front interface by vacuum sintering:

[0046] (1) Preparation of titanium-based (TiSe2 / TiO2) front interface: Ti3C2T x (i.e., titanium carbide (Ti3C2T) x MXene material and selenium powder were mixed in a molar ratio of 1:6, vacuum sealed in a quartz tube, and heated in a muffle furnace to 500°C for 50 h to obtain black front interface powder (i.e., TiSe2 / TiO2 front interface material).

[0047] (2) Electrode performance testing: The TiSe2 / TiO2 frontal interface material prepared in Example 1 was applied to the negative electrode of a zinc-ion battery, as follows:

[0048] The TiSe2 / TiO2 front interface material obtained in Example 1, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to prepare a slurry (i.e., the active material), which was then coated onto a 13mm diameter stainless steel foil current collector. After the solvent evaporated, the slurry was dried in a vacuum drying oven at 120°C for 10 hours. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled into a coin cell zinc-ion battery with an aqueous electrolyte (i.e., an aqueous solution of 3M zinc trifluoromethanesulfonate; the same below). Charge-discharge tests were conducted, with a voltage range of 0.05-1V.

[0049] The TiSe2 / TiO2 front interface material obtained in step (1) of Example 1 was characterized by scanning electron microscopy, and the results are as follows: Figure 1 As shown, the morphology of the material exhibits unique nanoflower characteristics.

[0050] The TiSe2 / TiO2 frontal interface material obtained in step (1) of Example 1 was characterized by transmission electron microscopy, and the results are as follows: Figure 3 As shown, the internal structure of the material exhibits unique porous characteristics (distinct from the external structure), which facilitates ion transport. Furthermore, Figure 3 A clear boundary line is visible between the interior and exterior of the material, which, in conjunction with the following text... Figure 5 It can be seen that the TiO2 component is loaded on TiSe2 (i.e., TiSe2 is the internal component of the material and TiO2 is the external component of the material), which indicates the successful synthesis of the TiSe2 / TiO2 front interface material.

[0051] X-ray diffraction (XRD) was performed on the TiSe2 / TiO2 frontal interface material prepared in step (1) of Example 1. The obtained XRD pattern is shown below. Figure 5As shown, by comparing the standard peak positions of TiSe2 and TiO2, it is not difficult to find that the TiSe2 / TiO2 front interface material prepared in step (1) of Example 1 has both TiSe2 and TiO2 components, and the TiSe2 / TiO2 front interface material was successfully prepared.

[0052] Coulomb efficiency diagram as follows Figure 7 As shown, through the following text Figure 8 By comparison, it is not difficult to find that the initial coulombic efficiency of the TiSe2 / TiO2 front interface prepared in Example 1 is greater than that of the pure TiSe2 material without a front interface in Comparative Example 1.

[0053] Cyclic voltammetry curves as shown Figure 9 As shown, through the following text Figure 10 By comparison, it is not difficult to find that the zinc ion insertion and extraction peaks of the TiSe2 / TiO2 front interface material prepared in Example 1 are significantly higher than those of the pure TiSe2 material without a front interface structure obtained in Example 1.

[0054] Charge-discharge curves as follows Figure 11 As shown, through the following text Figure 12 By comparison, it is not difficult to find that the charge-discharge curve of the TiSe2 / TiO2 leading edge interface material prepared in Example 1 is more stable than that of the pure TiSe2 material without leading edge interface structure obtained in Comparative Example 1, indicating that the TiSe2 / TiO2 leading edge interface material has a stable structure during charge and discharge.

[0055] AC impedance diagram as shown Figure 13 As shown, through the following text Figure 14 By comparison, it is not difficult to find that the TiSe2 / TiO2 front interface material prepared in Example 1 has a higher Warburg slope. The higher the Warburg slope, the better the ion spread (and the lower the resistivity). In other words, the resistance of the TiSe2 / TiO2 front interface material prepared in Example 1 is lower than that of the pure TiSe2 material without a front interface structure obtained in Comparative Example 1, and the conductivity is better.

[0056] Comparative Example 1

[0057] Preparation of pure TiSe2 materials:

[0058] (1) Preparation of titanium diselenide: Titanium powder and selenium powder are mixed in a molar ratio of 1:2, vacuum sealed in a quartz tube and heated in a muffle furnace to 500℃ for 50h to obtain dark red titanium diselenide powder.

[0059] (2) Electrode performance testing: The pure TiSe2 material prepared in Comparative Example 1 was applied to the negative electrode of a zinc-ion battery, as follows:

[0060] The pure TiSe2 material obtained in Comparative Example 1, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1 V.

[0061] The pure TiSe2 material without the TiSe2 / TiO2 leading edge interface obtained in step (1) of Comparative Example 1 was characterized by scanning electron microscopy, and the results are as follows: Figure 2 As shown, the material exhibits the characteristics of a typical hexagonal block structure.

[0062] Transmission electron microscopy was used to characterize the pure TiSe2 material without the TiSe2 / TiO2 leading edge interface obtained in step (1) of Comparative Example 1. The results are as follows: Figure 4 As shown, the internal structure of the material exhibits typical TiSe2 layered structure characteristics, but lacks porous features compared to TiSe2 / TiO2 frontal interface materials.

[0063] X-ray diffraction pattern as follows Figure 6 As shown, it can be seen that the material obtained in step (1) of Comparative Example 1 is a pure TiSe2 material without the TiSe2 / TiO2 front interface.

[0064] Coulomb efficiency diagram as follows Figure 8 As shown, the first coulombic efficiency of the pure TiSe2 material without the TiSe2 / TiO2 front interface obtained in Comparative Example 1 is lower than that of the TiSe2 / TiO2 front interface material.

[0065] Cyclic voltammetry curves as shown Figure 10 As shown, the zinc ion insertion and extraction peaks obtained in Comparative Example 1 without the TiSe2 / TiO2 leading interface material are not as obvious as those of the TiSe2 / TiO2 material with the leading interface.

[0066] Charge-discharge curves as follows Figure 12 As shown, the charge-discharge curves of the TiSe2 / TiO2 frontal interface material obtained in Comparative Example 1 are irreversible compared to those of the TiSe2 / TiO2 material with the frontal interface, indicating that the structure of the TiSe2 material is unstable during the charge-discharge process.

[0067] AC impedance diagram as shown Figure 14As shown, the resistance of the TiSe2 / TiO2 frontal interface material obtained in Comparative Example 1 without TiSe2 / TiO2 frontal interface material is greater than that of the TiSe2 / TiO2 material constructed with frontal interface, indicating that the TiSe2 material has poor conductivity.

[0068] Example 2

[0069] Preparation of copper-based (CuS / ZnS) front interface using vacuum sintering:

[0070] (1) Preparation of copper-based (CuS / ZnS) front interface: copper powder, zinc powder and sulfur powder are mixed in a molar ratio of 1:0.01:1, vacuum sealed in a quartz tube and heated to 900℃ for 50h in a muffle furnace to obtain black front interface powder.

[0071] (2) Electrode performance testing: The CuS / ZnS frontal interface material prepared in Example 2 was applied to the negative electrode of a zinc-ion battery, as follows:

[0072] The CuS / ZnS front interface material obtained in Example 2, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.15-0.9 V.

[0073] Comparative Example 2

[0074] Preparation of pure CuS materials:

[0075] (1) Preparation of copper sulfide body: copper powder and sulfur powder are mixed in a 1:1 molar ratio, vacuum sealed in a quartz tube and heated in a muffle furnace to 900℃ for 50h to obtain black copper sulfide powder.

[0076] (2) Electrode performance test: The pure CuS material prepared in Comparative Example 2 was applied to the negative electrode of a zinc-ion battery, as follows:

[0077] The pure CuS material obtained in Comparative Example 1, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.15-0.9 V.

[0078] Example 3

[0079] Plasma method for preparing the TiS2 / TiF4 front interface:

[0080] (1) TiS2 / TiF4 front interface: Titanium powder and sulfur powder were mixed in a molar ratio of 1:2, vacuum sealed in a quartz tube, and heated to 700℃ for 50h in a muffle furnace to obtain black titanium disulfide powder. The titanium disulfide powder was then placed in a plasma device and treated with carbon tetrafluoride plasma for 10min at a power of 100W to obtain the TiS2 / TiF4 front interface material.

[0081] (2) Electrode performance testing: The TiS2 / TiF4 leading-edge interface material prepared in Example 3 was applied to the negative electrode of a zinc-ion battery, as follows:

[0082] The TiS2 / TiF4 front interface material obtained in Example 3, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1 V.

[0083] Comparative Example 3

[0084] Preparation of pure TiS2:

[0085] (1) Preparation of pure TiS2: Titanium powder and sulfur powder were mixed in a molar ratio of 1:2, vacuum sealed in a quartz tube and heated to 700℃ for 50h in a muffle furnace to obtain black titanium disulfide powder.

[0086] (2) Electrode performance testing: The TiS2 material prepared in Comparative Example 3 was applied to the negative electrode of a zinc-ion battery, as follows:

[0087] The pure TiS2 material obtained in Comparative Example 3, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1 V.

[0088] Example 4

[0089] Preparation of BiOCl / Bi2O3 front interface by plasma method:

[0090] (1) BiOCl / Bi2O3 front interface:

[0091] First, following existing techniques, 0.7275 g of Bi(NO3)3·5H2O and 0.1785 g of KCl were dissolved in 16 mL of ethylene glycol and stirred for 30 minutes. The prepared solution was transferred to a 20 mL stainless steel autoclave and heated in an oven at 160 °C for 10 hours. The product was centrifuged, washed, and dried to obtain flower-shaped BiOCl powder.

[0092] Then, the BiOCl powder was placed in a plasma device and treated with oxygen plasma for 120 minutes at a power of 300W to obtain the BiOCl / Bi2O3 front interface material.

[0093] (2) Electrode performance testing: The BiOCl / Bi2O3 frontal interface material prepared in Example 4 was applied to the negative electrode of a zinc-ion battery, as follows:

[0094] The BiOCl / Bi2O3 front interface material obtained in Example 4, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1.5 V.

[0095] Comparative Example 4

[0096] Preparation of pure BiOCl:

[0097] (1) Preparation of pure BiOCl: 0.7275 g Bi(NO3)3·5H2O and 0.1785 g KCl were dissolved in 16 mL ethylene glycol and stirred for 30 minutes. The prepared solution was transferred to a 20 mL stainless steel autoclave and heated in an oven at 160 °C for 10 hours. The product was centrifuged, washed, and dried to obtain flower-shaped BiOCl powder.

[0098] (2) Electrode performance testing: The BiOCl material prepared in Comparative Example 4 was applied to the negative electrode of a zinc-ion battery, as follows:

[0099] The pure BiOCl interface material obtained in Comparative Example 4, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1.5 V.

[0100] Example 5

[0101] Preparation of tungsten-based (WO3 / ZnS) front interface using high-energy ball milling:

[0102] (1) Preparation of the tungsten-based (WO3 / ZnS) front interface: 2.5 mmol Na2WO3 was dissolved in 30 mL deionized water under stirring to form solution A. The pH of solution A was adjusted to 1.2 with 3M HCl. Then, 7 mmol oxalic acid was dissolved in 30 mL deionized water to form solution B. Solution B was then mixed with solution A to form a homogeneous solution, and 2 g (NH4)2SO4 was added to form solution C. Finally, solution C was transferred to a 100 mL autoclave and kept at 180 °C for 16 hours. After centrifugation, the solution was dried at 80 °C overnight and allowed to cool naturally to room temperature to obtain powder. The powder and ZnS were then placed in a high-energy ball mill at a speed of 500 r / min for 2 hours to obtain the final product.

[0103] (2) Electrode performance testing: The WO3 / ZnS frontal interface material prepared in Example 5 was applied to the negative electrode of a zinc-ion battery, as follows:

[0104] The WO3 / ZnS front interface material obtained in Example 5, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1 V.

[0105] Example 6

[0106] Preparation of tungsten-based (WO3 / ZnSe) front interface using high-energy ball milling:

[0107] (1) Preparation of the tungsten-based (WO3 / ZnSe) front interface: 2.5 mmol Na2WO3 was dissolved in 30 mL deionized water under stirring to form solution A. The pH of solution A was adjusted to 1.2 with 3M HCl. Then, 7 mmol oxalic acid was dissolved in 30 mL deionized water to form solution B. Solution B was then mixed with solution A to form a homogeneous solution, and 2 g (NH4)2SO4 was added to form solution C. Finally, solution C was transferred to a 100 mL autoclave and kept at 180 °C for 16 hours. After centrifugation, the solution was dried at 80 °C overnight and allowed to cool naturally to room temperature to obtain a powder. The powder and ZnSe were then placed in a high-energy ball mill at a speed of 1000 r / min for 50 h to obtain the final product.

[0108] (2) Electrode performance testing: The WO3 / ZnSe frontal interface material prepared in Example 6 was applied to the negative electrode of a zinc-ion battery, as follows:

[0109] The WO3 / ZnSe front interface material obtained in Example 6, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1 V.

[0110] Comparative Example 5

[0111] Preparation of pure WO3 materials:

[0112] (1) Preparation of pure WO3 material: 2.5 mmol Na2WO3 was dissolved in 30 mL deionized water under stirring to form solution A. The pH of solution A was adjusted to 1.2 with 3M HCl. Then, 7 mmol oxalic acid was dissolved in 30 mL deionized water to form solution B. Solution B was then mixed with solution A to form a homogeneous solution, and 2 g (NH4)2SO4 was added to form solution C. Finally, solution C was transferred to a 100 mL autoclave and kept at 180 °C for 16 hours. After centrifugation, the solution was dried overnight at 80 °C and allowed to cool naturally to room temperature to prepare a powder.

[0113] (2) Electrode performance test: The pure WO3 material prepared in Comparative Example 5 was applied to the negative electrode of a zinc-ion battery, as follows:

[0114] The pure WO3 material obtained in Comparative Example 5, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120°C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1V.

[0115] Example 7

[0116] Preparation of molybdenum-based (MoO2 / Zn3(PO4)2) front interface by high-energy ball milling:

[0117] (1) Preparation of the molybdenum-based (MoO2 / Zn3(PO4)2) front interface: 0.15 g of MoO3 was calcined in flowing H2 / Ar at 650 °C for 3 hours to obtain MoO2. The powder and Zn3(PO4)2 were placed in a high-energy ball mill and milled at 1500 r / min for 100 h to obtain the final product.

[0118] (2) Electrode performance testing: The MoO2 / Zn3(PO4)2 frontal interface material prepared in Example 7 was applied to the negative electrode of a zinc-ion battery, as follows:

[0119] The MoO2 / Zn3(PO4)2 front interface material obtained in Example 7, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120 °C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.2-1.2 V.

[0120] Example 8

[0121] Preparation of molybdenum-based (MoO2 / ZnB4O7) front interface using high-energy ball milling:

[0122] (1) Preparation of molybdenum-based (MoO2 / ZnB4O7) front interface: 0.15 g of MoO3 was calcined in flowing H2 / Ar at 650 °C for 3 hours to obtain MoO2. The powder and ZnB4O7 were placed in a high-energy ball mill and milled at 1500 r / min for 40 h to obtain the final product.

[0123] (2) Electrode performance testing: The MoO2 / ZnB4O7 leading interface material prepared in Example 8 was applied to the negative electrode of a zinc-ion battery, as follows:

[0124] The MoO2 / ZnB4O7 front interface material obtained in Example 8, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120°C for 10 hours. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.2-1.2V.

[0125] Comparative Example 6

[0126] Preparation of pure MoO2 materials:

[0127] (1) Preparation of pure MoO2 material: 0.15g MoO3 was calcined in flowing H2 / Ar at 650℃ for 3 hours to obtain MoO2.

[0128] (2) Electrode performance test: The pure MoO2 material prepared in Comparative Example 6 was applied to the negative electrode of a zinc-ion battery, as follows:

[0129] The pure WO3 material obtained in Comparative Example 6, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13 mm diameter stainless steel foil. After the solvent evaporated, the foil was placed in a vacuum drying oven and dried at 120°C for 10 h. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.2-1.2 V.

[0130] Example 9

[0131] Direct coating method for constructing vanadium-based (VO) x / C) Preparation of the frontal interface:

[0132] (1) Vanadium-based (VO x / C) Preparation of the frontier interface: 0.5 g of V2O5 was calcined at 650 °C for 1.5 hours in a flowing H2 / Ar (using a commercially available mixture of hydrogen and argon) to obtain V2O5. x The VO obtained in Example 9 x Materials, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly in a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a stainless steel foil with a diameter of 13 mm. After the solvent evaporated, the slurry was placed in a vacuum drying oven and dried at 120°C for 10 hours to obtain the electrode sheet.

[0133] Next, commercial activated carbon powder, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly in a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry, which was then coated onto the electrode (completely covering the active material layer; closer to the electrolyte side than the active material layer). After the solvent evaporated, the electrode was placed in a vacuum drying oven and dried at 120°C for 10 hours.

[0134] (2) Electrode performance test: The VO prepared in Example 9 was tested. x / C-frontier interface materials are applied to the anode of zinc-ion batteries, as follows:

[0135] The VO obtained in Example 9 x The / C leading-edge interface electrode was assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing, with a voltage range of 0.05-1.2V.

[0136] Comparative Example 7

[0137] Pure VO x Material preparation:

[0138] (1) Pure VO x Material preparation: 0.5 g of V₂O₅ was calcined in flowing H₂ / Ar at 650 °C for 1.5 hours to obtain VO₂O₅. x The VO obtained in Comparative Example 7 x Materials, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly in a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a stainless steel foil with a diameter of 13 mm. After the solvent evaporated, the mixture was placed in a vacuum drying oven and dried at 120°C for 10 hours.

[0139] (2) Electrode performance test: The pure VO prepared in Comparative Example 7 was used... x The material is used in the negative electrode of zinc-ion batteries, specifically as follows:

[0140] The pure VO obtained in Comparative Example 7 x The material electrodes were assembled with an aqueous electrolyte into a coin cell zinc-ion battery for charge-discharge testing, with a voltage range of 0.05-1.2V.

[0141] Example 10

[0142] Preparation of titanium-based (TiSe2 / TiO2) front interface by tube furnace calcination:

[0143] (1) Preparation of titanium-based (TiSe2 / TiO2) front interface: TiSe2 and TiO2 are mixed in a molar ratio of 12:1. The material is calcined at high temperature under an argon atmosphere, heated to 500°C and held for 6 hours to obtain black front interface powder.

[0144] (2) Electrode performance testing: The TiSe2 / TiO2 frontal interface material prepared in Example 10 was applied to the negative electrode of a zinc-ion battery, as follows:

[0145] The TiSe2 / TiO2 front interface material obtained in Example 10, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13mm diameter stainless steel foil current collector. After the solvent evaporated, the slurry was dried in a vacuum drying oven at 120°C for 10 hours. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1V.

[0146] Example 11

[0147] Preparation of titanium-based (TiSe2 / TiO2) front interface by tube furnace calcination:

[0148] (1) Preparation of titanium-based (TiSe2 / TiO2) front interface: TiSe2 and TiO2 are mixed in a molar ratio of 12:1. The material is calcined at high temperature under an argon atmosphere, heated to 900℃ and held for 6 hours to obtain black front interface powder.

[0149] (2) Electrode performance testing: The TiSe2 / TiO2 frontal interface material prepared in Example 11 was applied to the negative electrode of a zinc-ion battery, as follows:

[0150] The TiSe2 / TiO2 front interface material obtained in Example 11, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of NMP was added to make a slurry (i.e., the active material), which was then coated onto a 13mm diameter stainless steel foil current collector. After the solvent evaporated, the slurry was dried in a vacuum drying oven at 120°C for 10 hours. Then, the stainless steel foil coated with the active material was used as the working electrode and assembled with an aqueous electrolyte to form a coin cell zinc-ion battery for charge-discharge testing. The voltage range was 0.05-1V.

[0151] The rocking chair coin zinc-ion batteries constructed in each embodiment and each comparative embodiment were tested, and the discharge capacity, initial coulombic efficiency, and 0.5A g were obtained. -1 The capacity retention results after 1000 cycles are shown in Tables 1, 2, and 3.

[0152] Table 1. Discharge capacity before and after constructing the leading edge interface.

[0153]

[0154]

[0155] Table 2. Initial Coulomb efficiency before and after constructing the frontier interface.

[0156] Example 1 78 Comparative Example 1 12 Example 2 90 Comparative Example 2 26 Example 3 77 Comparative Example 3 24 Example 4 86 Comparative Example 4 14 Example 5 79 Comparative Example 5 26 Example 6 72 Example 7 77 Comparative Example 6 44 Example 8 71 Example 9 87 Comparative Example 7 22 Example 10 65 Example 11 60

[0157] Table 3 Capacity retention rate before and after constructing the frontal interface

[0158]

[0159]

[0160] As can be seen from Tables 1, 2, and 3, based on this invention, a leading interface can be constructed on the traditional rocking-chair zinc anode material through different methods. This can effectively alleviate the side reactions at the rocking-chair zinc anode interface, reduce the direct contact between the anode and water molecules in the electrolyte, further improve capacity, suppress side reactions on the anode surface, and improve cycle performance.

[0161] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A rocking chair-type aqueous zinc-ion battery negative electrode composite material, characterized in that, This composite material was obtained by loading and / or modifying the interfacial material composition on the negative electrode active material of a rocking chair zinc-ion battery; wherein, The interface material is electrochemically inert and stable in the aqueous electrolyte, and does not provide capacity. The interface material is selected from at least one of activated carbon, TiO2, ZnS, ZnSe, Bi2O3, TiF4, Zn3(PO4)2, and ZnB4O7; The rocking chair zinc-ion battery negative electrode active material is at least one of the following: titanium-based rocking chair zinc-ion battery negative electrode active material, copper-based rocking chair zinc-ion battery negative electrode active material, bismuth-based rocking chair zinc-ion battery negative electrode active material, molybdenum-based rocking chair zinc-ion battery negative electrode active material, tungsten-based rocking chair zinc-ion battery negative electrode active material, and vanadium-based rocking chair zinc-ion battery negative electrode active material.

2. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 1, characterized in that, The rocking chair-type aqueous zinc-ion battery anode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery anode active material using a vacuum sintering method.

3. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 2, characterized in that, The sintering temperature used in the vacuum sintering method is 500℃ ~ 900℃.

4. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 1, characterized in that, The rocking chair-type aqueous zinc-ion battery negative electrode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery negative electrode active material through plasma treatment.

5. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 4, characterized in that, The plasma treatment uses a power of 100 W to 300 W and a treatment time of 10 min to 120 min.

6. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 1, characterized in that, The rocking chair-type aqueous zinc-ion battery anode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery anode active material using a high-energy ball milling method.

7. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 6, characterized in that, The high-energy ball milling method uses a rotation speed of 500 r / min to 1500 r / min and a processing time of 2 h to 100 h.

8. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 1, characterized in that, The rocking chair-type aqueous zinc-ion battery negative electrode composite material is obtained by first coating the rocking chair-type zinc-ion battery negative electrode active material on one side of the current collector, and then coating the interface material component on the same side of the current collector to cover the rocking chair-type zinc-ion battery negative electrode active material.

9. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 1, characterized in that, The rocking chair-type aqueous zinc-ion battery anode composite material is obtained by modifying the interface material composition on the surface and / or interface of the rocking chair-type zinc-ion battery anode active material under inert atmosphere by using a tube furnace calcination method.

10. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 9, characterized in that, The sintering temperature used in the tubular furnace calcination method is 500°C. o C ~ 900 o C; The inert atmosphere is argon.

11. The rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in claim 1, characterized in that, The discharge capacity of the negative electrode composite material of the rocking chair-type aqueous zinc-ion battery is 200 ~ 280 mAh g. -1 The initial coulomb efficiency is 60-90%, and it can achieve a coulomb efficiency of 0.5 Ag. -1 It has a capacity retention of 62-90% after 1000 cycles.

12. The application of the rocking chair-type aqueous zinc-ion battery negative electrode composite material as described in any one of claims 1-11 as the negative electrode of the rocking chair-type aqueous zinc-ion battery.

Citation Information

Patent Citations

  • Zinc-based battery anode material containing Bi2O3 with self-assembled structure and preparation method

    CN108539169A

  • Zinc negative electrode material with double modification layers on surface, preparation method of zinc negative electrode material and application of zinc negative electrode material in aqueous zinc ion battery

    CN114243019A